Determinan Nilai Perusahaan Pada Perusahaan Sektor Property yang Terdaftar Di BEI Periode 2017-2021 - Rizal Hanif Musthofa; Kartika Hendra Titisari; Purnama Siddi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The property sector industry is one of the industries that is useful for the activities of the Indonesian people, because this industrial sector has investment value that is quite attractive, it is assessed that the changes are constant or consistent and can increase the value of the company. This observation intends to investigate the effect of profitability, capital structure, debt policy, and company size on firm value in companies with the aim of providing empirical evidence regarding profitability, capital structure, debt policy, and company size in projecting firm value through testing of each variable. The objects of this observation are property sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The sample selection method used was purposive sampling of 15 companies. The type of analysis performed on this observation is a multiple linear regression model whose observations show that 1) profitability affects firm value, 2) capital structure has no effect on firm value, 3) debt policy affects firm value, and 4) size company effect on firm value. Keywords: Profitability, Capital Structure, Debt Policy, Firm Size, Firm Value